2010
DOI: 10.3233/jad-2010-1365
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Activation of Astrocytes by Amyloid-β is Potentiated by Pro-Oxidant Agents

Abstract: Alzheimer's disease (AD) is a devastating age-related neurodegenerative disease. Age is the main risk factor for sporadic AD, which is the most prevalent type. Amyloid-beta peptide (Abeta) neurotoxicity is the proposed first step in a cascade of deleterious events leading to AD pathology and dementia. Glial cells play an important role in these changes. Astrocytes provide vital support to neurons and modulate functional synapses. Therefore, the toxic effects of Abeta on astrocytes might promote neurodegenerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 60 publications
0
32
0
Order By: Relevance
“…The brain, with high oxygen demand, and relatively deficient in anti-oxidative defense, is the most susceptible organ to oxidative damage. Studies with D-gal-lesioned mice have demonstrated that D-gal-induced oxidative stress is a potent inducer of apoptosis (García-Matas et al, 2010;Recuero et al, 2009;Ritchie, 2009). In the present study, we also found that D-gal induced an increase in ROS generation and lipid peroxidation, and concomitantly increase of apoptosis, further suggesting that there is a close relationship between oxidative stress and brain injury.…”
Section: Discussionmentioning
confidence: 97%
“…The brain, with high oxygen demand, and relatively deficient in anti-oxidative defense, is the most susceptible organ to oxidative damage. Studies with D-gal-lesioned mice have demonstrated that D-gal-induced oxidative stress is a potent inducer of apoptosis (García-Matas et al, 2010;Recuero et al, 2009;Ritchie, 2009). In the present study, we also found that D-gal induced an increase in ROS generation and lipid peroxidation, and concomitantly increase of apoptosis, further suggesting that there is a close relationship between oxidative stress and brain injury.…”
Section: Discussionmentioning
confidence: 97%
“…Apart from its effects on the endothelial cells, another mechanism by which oxidative stress disrupts BBB is by damaging the astrocytes. Oxidative stress is an important cause of both the activation of astrocyte and the Ab production (Garcia-Matas et al 2010;Matos et al 2008). Oxidative stress and damaged astrocytes may promote BBB disruption in AD because tight junctions within the BBB are also enveloped by astrocytic end feet.…”
Section: Bbb Astrocyte and Abmentioning
confidence: 99%
“…However, melatonin treatment at old age in Tg2576 mice did not afford protection against oxidative damage (Quinn et al 2005). Oxidative damage is a biochemical hallmark of AD and a possible link between aging and AD (Castellani et al, 2008;García-Matas et al, 2010). Oxidative-stress-related derangements of neurotransmission and general brain function in aging and AD could be prevented or delayed by physical exercise and/or melatonin or other potent antioxidants and enhancers of antioxidant cell defenses.…”
mentioning
confidence: 99%